Multidisciplinary Conservative Treatment of Difficult Bile Duct Stones: A Real Alternative to Surgery. Issue 4 (1997) - Masci, E.; Fanti, L.; Mariani, A.; Spagnolo, S.; Zuliani, W.; Castrucci, M.; Testoni, P. A.; Tittobello, A.
Abstract : 56 patients with large CBD or intrahepatic stones underwent endoscopic and/or percutaneous treatment followed by extracorporeal shock wave lithotripsy. Percutaneous access to the biliary tract was chosen when an endoscopic approach was not possible (hepaticojejunostomy in 5 patients, 1 juxtapapillary diverticulum and I inflammatory bile duct stricture). Visualization of stones was achieved radiologically in 32 patients and by ultrasound in 24. The procedure was successful in 47 of 56 treated patients (83.9%). Clearance of the biliary tract was obtained in 25 cases (53%), whereas in 22 cases (47%) complete clearing of biliary tract was obtained only after endoscopic extraction of fragments (17 cases) or percutaneous (5 cases). The median number of shock waves in each session was 1725 (range 300–3166), which were applied during one (n=30), two (n=22) or three sessions (n=4). The only complications were 1 case of symptomatic hyperamylasemia and 3 cases of macrohematuria. In conclusion, extracorporeal lithotripsy combined with endoscopic and/or percutaneous treatment is a real alternative to surgery for difficult stones.